Government Liability in State Financial Management for the Procurement of Goods and Services During the COVID-19 Pandemic: Pertanggungjawaban Pemerintah Terkait Pengelolaan Keuangan Negara Dalam Penyediaan Barang dan Jasa di Masa Covid-19 - Rini Maisari (Lex Renaissance, 2024)
The government's accountability in managing state finances in the procurement of goods and services sector during the Covid-19 pandemic shows that the government's accountability and transparency in using APBN funds is still weak. This is reviewed from the findings made by the Indonesian Corruption Watch (ICW) regarding the management of state finances in the procurement of goods such as test kits, medicines, and health materials in handling Covid, the procedures and mechanisms of which were not conveyed to the public. This problem arises because the government is given discretion to act, especially during a pandemic where the country is in a state of emergency, which increases the opportunity for abuse of power by public officials. This study aims to review how the government is accountable for the procurement of goods and services during the Covid-19 pandemic. This research is normative legal research with a statutory and conceptual approach. The results of the study show that government accountability in the financial sector during the pandemic has not shown optimal results because the government thought of hiding information to prevent public panic and the lack of awareness of public officials in being accountable for the use of state finances. This is certainly contrary to several laws that require transparency and accountability, the failure to implement the principles of good governance, and the failure to accommodate the fulfillment of citizens' basic rights to access information openly.Keywords: Accountability, Procurement of Goods and Services, Covid-19 Pandemic AbstrakPertanggungjawaban pemerintah dalam pengelolaan keuangan negara di sektor pengadaan barang dan jasa saat pandemi covid-19 menunjukkan masih lemahnya akuntabilitas dan transparansi pemerintah dalam menggunakan dana APBN. Hal tersebut ditinjau dari temuan yang dilakukan oleh Indonesian Corruption Watch (ICW) terkait pengelolaan keuangan negara pada pengadaan barang seperti alat uji, obat, hingga alat material kesehatan dalam penanganan covid yang prosedur maupun mekanismenya tidak disampaikan kepada publik. Persoalan ini muncul karena pemerintah dibekali diskresi untuk bertindak khususnya saat masa pandemi karena negara dalam kondisi darurat sehingga menyebabkan peluang penyalahgunaan kekuasaan semakin besar dilakukan oleh pejabat publik. Penelitian ini bertujuan untuk meninjau pertanggungjawaban pemerintah pada pengadaan barang dan jasa di masa pandemi covid-19. Penelitian ini adalah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa pertanggungjawaban pemerintah di sektor keuangan di masa pandemi belum menunjukkan hasil yang optimal karena adanya pemikiran pemerintah untuk menyembunyikan informasi guna mencegah kepanikan masyarakat hingga tidak adanya kesadaran dari pejabat publik dalam mempertanggungjawabkan penggunaan keuangan negara. Hal ini tentu bertentangan dengan sejumlah undang-undang yang menghendaki adanya transparansi, akuntabilitas dan terselenggaranya prinsip good governance sehingga tidak mewadahi pemenuhan hak asasi warga negara dalam mengakses informasi secara terbuka.Kata Kunci: Pertanggungjawaban, Pengadaan Barang dan Jasa, Pandemi Covid-19